2014
DOI: 10.1089/thy.2014.0052
|View full text |Cite
|
Sign up to set email alerts
|

Thyroglobulin as a Biomarker of Iodine Deficiency: A Review

Abstract: Background: Thyroglobulin, produced exclusively by the thyroid gland, has been proposed to be a more sensitive biomarker of iodine status than thyrotropin or the thyroid hormones triiodothyronine and thyroxine. However, evidence on the usefulness of thyroglobulin (Tg) to assess iodine status has not been extensively reviewed, particularly in pregnant women and adults. Summary: An electronic literature search was conducted using the Cochrane CENTRAL, Web of Science, PubMed, and Medline to locate relevant studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
2
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(134 citation statements)
references
References 92 publications
4
113
2
9
Order By: Relevance
“…In accordance with our results, these studies found an inverse relation between serum Tg and iodine intake even in regions with small differences in iodine intake. Several studies concluded that even if serum Tg concentration is a non-specific marker of thyroid disease in the individual and even if Tg-Ab may influence measurements, Tg is a good marker of iodine intake in a population and that it is a useful tool in monitoring the iodine status (14,18,21,28,29). However, only one previous longitudinal population-based cohort study has investigated serum Tg in relation to iodine intake.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In accordance with our results, these studies found an inverse relation between serum Tg and iodine intake even in regions with small differences in iodine intake. Several studies concluded that even if serum Tg concentration is a non-specific marker of thyroid disease in the individual and even if Tg-Ab may influence measurements, Tg is a good marker of iodine intake in a population and that it is a useful tool in monitoring the iodine status (14,18,21,28,29). However, only one previous longitudinal population-based cohort study has investigated serum Tg in relation to iodine intake.…”
Section: Previous Studiesmentioning
confidence: 99%
“…In contrast, high thyroid volume is an indicator of longterm iodine deficiency that may persist for years after iodine repletion (Zimmermann et al, 2006). Serum thyroglobulin (Tg), a thyroid protein that facilitates the uptake and storage of iodine in the thyroid gland, has been proposed as a biomarker of intermediate-term population iodine nutrition status (weeks to months) based on associations with UIC (Knudsen et al, 2001;Krejbjerg et al, 2016;Swanson et al, 2012;Vejbjerg et al, 2009), and sensitivity to changes in iodine status following iodine supplementation (Gordon et al, 2009;Ma and Skeaff, 2014;Skeaff and Lonsdale-Cooper, 2013;Vejbjerg et al, 2009;Zimmermann et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Тиреоглобулин предлагается как перспективный биомаркер для оценки дефицита йода в регионе [6]. Большинством исследований рекомендуется исполь-зование ТГ в качестве биомаркера йодного статуса у школьников с использованием порога <13 мкг/л [7].…”
Section: Discussionunclassified
“…Имеются многочисленные исследования роли ТГ в качестве биомаркера дефицита йода [6]. Так как у детей практически не встречаются АтТГ, его кон-центрация показывает истинную картину йододе-фицита в регионе.…”
Section: Discussionunclassified
See 1 more Smart Citation